An autophagy‐related long non‐coding RNA signature for glioma. Issue 4 (5th March 2019) - Luan, Fangkun; Chen, Wenjie; Chen, Miao; Yan, Jun; Chen, Hao; Yu, Haiyue; Liu, Tieqi; Mo, Ligen
Abstract : Glioma is one of the most common types of malignant primary central nervous system tumor, and prognosis for this disease is poor. As autophagic drugs have been reported to induce glioma cell death, we investigated the potential prognostic role of autophagy‐associated long non‐coding RNA (lncRNA) in glioma patients. In this study, we obtained 879 lncRNAs and 216 autophagy genes from the Chinese Glioma Genome Atlas microarray, and found that 402 lncRNAs are correlated with the autophagy genes. Subsequently, 10 autophagy‐associated lncRNAs with prognostic value ( PCBP1‐AS1, TP53TG1, DHRS4‐AS1, ZNF674‐AS1, GABPB1‐AS1, DDX11‐AS1, SBF2‐AS1, MIR4453HG, MAPKAPK5 ‐AS1 and COX10‐AS1 ) were identified in glioma patients using multivariate Cox regression analyses. A prognostic signature was then established based on these prognostic lncRNAs, dividing patients into low‐risk and high‐risk groups. The overall survival time was shorter in the high‐risk group than that in the low‐risk group [hazard ratio (HR) = 5.307, 95% CI: 4.195–8.305; P < 0.0001]. Gene set enrichment analysis revealed that the gene sets were significantly enriched in cancer‐related pathways, including interleukin (IL) 6/Janus kinase/signal transducer and activator of transcription (STAT) 3 signaling, tumor necrosis factor α signaling via nuclear factor κB, IL2/STAT5 signaling, the p53 pathway and the KRAS signaling pathway. The Cancer Genome Atlas dataset was used to validate that high‐risk patients have worse survival outcomes than low‐risk patients (HR = 1.544, 95% CI: 1.110–2.231; P = 0.031). In summary, our signature of 10 autophagy‐related lncRNAs has prognostic potential for glioma, and these autophagy‐related lncRNAs may play a key role in glioma biology. Abstract : Here, we identified a 10 autophagy‐associated long non‐coding RNA (lncRNA) signature with prognostic value in glioma patients, by using a Chinese Glioma Genome Atlas microarray. Gene sets based on the signature were significantly enriched in cancer‐related pathways. Our 10 autophagy‐related lncRNA signature may have prognostic potential for glioma.